Experimental Investigation on Mechanical Behaviour of Kevlar and Ramie Fibre Reinforced Epoxy Composites. (2nd February 2022) - Vedanarayanan, V.; Kumar, B. S. Praveen; Karuna, M. S.; Jayanthi, A.; Kumar, K. V. Pradeep; Radha, A.; Ramkumar, G.; Christopher, David
Abstract : Natural fibre composites have been replacing synthetic fibre composites in practical applications for the last several years because of the features such as low densities, low weight, relatively inexpensive, recyclability, and excellent mechanical qualities unique to the substance. Thus, the current study examines how Kevlar/Ramie/Nano SiC hybrid fibre reinforced composites are made and their mechanical properties, and it compares them to those made using a single natural fibre reinforced composite. It was found that natural fibre composite densities and hardness were all within acceptable ranges by performing composites' tensile and flexural strength tests. The hand-lay-up technique used ASTM standards samples to construct the composite specimens with various fibre weight percentages. Increase in mechanical characteristics was achieved by adding the glass and the epoxy fibres into the epoxy matrix. The hybrid composite's performance is promising, especially those of individual fibre-reinforced composites.